2004
DOI: 10.1007/s00405-004-0799-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental vibratory damage of the inner ear

Abstract: The aim of the experiment was to determine the effect of whole-body vibration on the inner ear. The investigations were carried out on 40 guinea pigs, subjected to sinusoidal vibration (10 Hz/5 mm/1.4 g rms) for 1 to 6 months in a noiseless apparatus. Cochlear microphonic measurements were done with a phase-sensitive detection technique for the levels 70, 80 and 90 dB and the frequencies of 0.26, 0.5, 1 and 2 kHz from the apex of the cochlea and for 4 and 8 kHz from the region of the round window. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Hamernik et al (1989) found that histological changes in the extent of the outer hair cell loss were responsible for the cochlear function shifts that occurred following vibration exposure conditions [11]. Bochnia et al (2005) asserted that vibration-induced changes were seen in all the examined inner ear areas, whereas hair-cell damage was more often seen in the apex, spreading gradually to the base and from the circumference (outer hair cells of the third row) to the modiolus [13]. Hamernik et al (1980) found that a damaged cochlea and vibrated membranous labyrinth were the main causes for vibration-induced cochlear function changes after low-frequency vibration [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hamernik et al (1989) found that histological changes in the extent of the outer hair cell loss were responsible for the cochlear function shifts that occurred following vibration exposure conditions [11]. Bochnia et al (2005) asserted that vibration-induced changes were seen in all the examined inner ear areas, whereas hair-cell damage was more often seen in the apex, spreading gradually to the base and from the circumference (outer hair cells of the third row) to the modiolus [13]. Hamernik et al (1980) found that a damaged cochlea and vibrated membranous labyrinth were the main causes for vibration-induced cochlear function changes after low-frequency vibration [9].…”
Section: Discussionmentioning
confidence: 99%
“…Soliman et al (2003) reported that the exposure to vibration only led to enhancement of both DPOAE amplitude and signal to noise ratio [12]. Bochnia et al (2005) showed that vibration-induced damages to the inner ear structures may cause a worsening of hearing, especially at low and medium frequencies [13]. Therefore, a significant gap is evident in understanding the result of WBV exposure on cochlear function at realistic levels typically found in industrial settings.…”
Section: Introductionmentioning
confidence: 99%
“…Our results add further evidence that the head has a natural frequency between 20 and 30 Hz, and this frequency value may vary between individuals and the posture adopted. Since excessive vibration energy may have a detrimental effect on the visual, 16,17 auditory, 46 and vestibular systems, 47 these frequencies should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of previous studies reported that vibration transferred to the body caused adverse effects such as nausea and headache due to impaired vision, hearing loss, and strong stimuli to organs as vibration frequency increased [3537]. In this study, RPE was highest at 22.67 at the frequency of 26 Hz, and some subjects complained of slight nausea and headache when WBV was applied at 26 Hz; they felt some pain at the knee joint and skin, had mild visual impairments, and had difficulty listening to the instructions of a computer program due to noises.…”
Section: Discussionmentioning
confidence: 99%